Perceived Greenwash and Green Trust of Danone-Aqua as B Corporation Certified Company in Indonesia - Kristia Kristia (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
Amidst customers' growing awareness regarding their consumption's influence on environmental sustainability in consumption processes, many businesses must take necessary actions to maintain consumer trust that they embrace the same environmentally responsible values as customers. Greenwashing, which involves making misleading statements about a company's pro-environmental stance or failing to meet a commitment to lessen negative environmental impacts, has significantly eroded consumer trust. This study investigated the influence of perceived greenwashing on environmental trust and the mediating effect of perceived green risk and perceived green value. This study's sample consisted of 200 respondents selected using a method of purposive sampling based on the criterion of Generation Z members with knowledge of greenwashing methods and the B Corporation accreditation awarded to Danone-Aqua Indonesia. The data processing approach employs the SEM-PLS technique with the SmartPLS 3.0 application. The study results indicate that perceived greenwash has no significant effect on green trust, but the effect becomes significant when perceived green risk and value are present as mediating variables. Therefore, in order to maintain consumer trust in the company's performance in preserving the environment, Danone-AQUA is encouraged to make continuous efforts to increase customer perceived value and minimize the perceived risks that consumers experienced, including maintaining the B Corporation Accredition value excellent, amidst circulating greenwashing concerns.